2014
DOI: 10.1038/nature13391
|View full text |Cite
|
Sign up to set email alerts
|

Possible control of subduction zone slow-earthquake periodicity by silica enrichment

Abstract: Seismic and geodetic observations in subduction zone forearcs indicate that slow earthquakes, including episodic tremor and slip, recur at intervals of less than six months to more than two years. In Cascadia, slow slip is segmented along strike and tremor data show a gradation from large, infrequent slip episodes to small, frequent slip events with increasing depth of the plate interface. Observations and models of slow slip and tremor require the presence of near-lithostatic pore-fluid pressures in slow-eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
215
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(233 citation statements)
references
References 43 publications
15
215
2
1
Order By: Relevance
“…It has been shown that foliated serpentine has anisotropic permeability that could focus fluid flow parallel to the slab up to the tip of the forearc mantle wedge (Kawano, et al 2011). The plate interface could also be sealed by precipitation of solutes such as silica, and episodically opened by large seismic events, as suggested for Cascadia (Hyndman, et al 2015) and other subduction zones (Audet and Burgmann 2014). The presence of fluids in the subducting oceanic crust is also suggested by high-conductivity anomalies parallel to the slab (Wannamaker, et al 2014), and is substantiated by extensive geochemical investigations of high-pressure ophiolitic terranes (Bebout and Penniston-Dorland 2016;.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that foliated serpentine has anisotropic permeability that could focus fluid flow parallel to the slab up to the tip of the forearc mantle wedge (Kawano, et al 2011). The plate interface could also be sealed by precipitation of solutes such as silica, and episodically opened by large seismic events, as suggested for Cascadia (Hyndman, et al 2015) and other subduction zones (Audet and Burgmann 2014). The presence of fluids in the subducting oceanic crust is also suggested by high-conductivity anomalies parallel to the slab (Wannamaker, et al 2014), and is substantiated by extensive geochemical investigations of high-pressure ophiolitic terranes (Bebout and Penniston-Dorland 2016;.…”
Section: Discussionmentioning
confidence: 94%
“…The two most simple mechanisms to explain the weakening of the plate interface and the transition to stable-sliding with increasing distance from the trench are increasing temperatures with depth and increased pore-pressure from fluids released through metamorphic dehydration. Recent studies (Shelly et al, 2006;Audet et al, 2009;Song et al, 2009;Kim et al, 2010;Audet and Bürgmann, 2014) have suggested that trapped fluids at the plate interface and the consequent high pore pressures are the most important factor in creating the weak plate interface necessary for slow earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic micro-and macrostructural field studies [e.g., Faulkner et al, 2006;Dor et al, 2006;Mitchell and Faulkner, 2009;Savage and Brodsky, 2011], as well as seismic surveys [e.g., Li et al, 2006;Cochran et al, 2009;Froment et al, 2014], have recently been performed on fault zones, a key component to understanding the energy balance of earthquakes [e.g., Rice, 2002;Kanamori, 2006]. Relating fault mechanics to fault zone structure, several authors have underlined the importance of combining field observations with geodetic and seismological measurements to understand what controls the seismic and aseismic slip behavior [e.g., Biegel and Sammis, 2004;Thomas et al, 2014;Audet and Burgmann, 2014]. Recent studies have successfully bridged the gap between rocks physics, laboratory experiments, and seismic observations of dynamic processes and fault zone evolution [e.g., Schubnel et al, 2006;Brantut, 2015].…”
Section: Library Of Congress Cataloging-in-publicationmentioning
confidence: 99%